Principals' Strategies To Improve The Quality Of Education: A Qualitative Research At SMA Negeri 1 West Pemulutan - Edi Harapan; Tri Aprina; Darwin Effendi (International Journal of Education, Vocational and Social Science, 2024)
The study aims to describe the principal's strategy to improve the quality of education at SMA Negeri 1 West Pemulutan. Research using qualitative methods. Research informants are principals, educators and education personnel. Data collection techniques use observation, interviews and documentation. Test the validity of data using credibility, transferability, dependability and confirmability testing methods. The data analysis technique used is a Spradley model with stages of analysis of domain, taxonomy, componential and cultural themes. The results of the study stated that the principal's strategy is to improve the quality of education through fostering teacher discipline and education staff, providing motivation to teachers, rewarding teachers and education staff, seeking the availability of facilities and infrastructure as supporting facilities, MGMP, participating in teacher mobilization programs, participating in further studies, and the use of technology in learning. This strategy is very effectively used by SMA Negeri 1 West Pemulutan which can increase accreditation from C to B.